Characteristics of betatron radiation from direct-laser accelerated electrons - Huang, T; Robinson, A; Zhou, C; Qiao, B; Liu, B; Shang-Chen, R; Xian-Tu, H; Norreys, P (American Physical Society, 2016)
Betatron radiation from direct-laser accelerated electrons is characterized analytically and numerically. It is shown here that the electron dynamics is strongly dependent on a self-similar parameter S(≡ne/nca0). Both the electron transverse momentum and energy are proportional to the normalized amplitude of laser field (a0) for a fixed value of S. As a result, the total number of radiated photons scales as a2/0/√S and the energy conversion efficiency of photons from the accelerated electrons scales as a3/0/S. The particle-in-cell simulations agree well with the analytical scalings. It is suggested that a tunable high-energy and high-flux radiation source can be achieved by exploiting this regime.